AVALIAÇÃO DO PERCENTUAL DE SACAROSE EM TRÊS CULTIVARES E QUATRO DENSIDADES DE CANA - Abreu, Fernando B. d.; Quadros, Valmir J. d.; Buratti, João V.; Silva, José A. G. d.; Kerpel, Lucas A.; Fiorin, Carlos (Salão do Conhecimento, 2013)
Resumo